2008
DOI: 10.1177/0146167208321268
|View full text |Cite
|
Sign up to set email alerts
|

Kicking the (Barking) Dog Effect: The Moderating Role of Target Attributes on Triggered Displaced Aggression

Abstract: Sometimes aggression is displaced onto a target who is not totally innocent, but emits a mildly irritating behavior called a triggering event. In three studies we examine stable personal attributes of targets that can impact such triggered displaced aggression (TDA). Lower levels of TDA were directed to targets whose attitudes were similar as compared to dissimilar to those of the actor (Experiment 1), and to targets who were in-group as compared to out-group members (Experiment 2). Conceptually replicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…It is also possible that objectifying girls stigmatizes them, which is then perceived as a negative attribute or characteristic of those individuals. This process has important implications for the facilitation of aggression because it has been shown that provoked individuals are more aggressive towards their target when the latter possess negative characteristics, such as out-group membership (Pedersen,16 Bushman, Vasquez, & Miller, 2008). Thus, the stigma induced by objectification may be perceived as a negative characteristic of the objectified, which subsequently primes objectifying individuals for more intense aggressive response.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that objectifying girls stigmatizes them, which is then perceived as a negative attribute or characteristic of those individuals. This process has important implications for the facilitation of aggression because it has been shown that provoked individuals are more aggressive towards their target when the latter possess negative characteristics, such as out-group membership (Pedersen,16 Bushman, Vasquez, & Miller, 2008). Thus, the stigma induced by objectification may be perceived as a negative characteristic of the objectified, which subsequently primes objectifying individuals for more intense aggressive response.…”
Section: Discussionmentioning
confidence: 99%
“…In prior research, in-group membership decreased TDA such that the TDA in this condition was at the same levels as in the no-trigger conditions (Pedersen et al, 2006). Expecting personalization and differentiation to have little effect on aggression toward in-group members, we therefore focused on a condition that elicits higher baseline levels of aggression-an outgroup target condition-thereby increasing the likelihood of interesting results.…”
Section: Participants and Designmentioning
confidence: 98%
“…As noted, researchers have invoked prejudice 1 and negative priming (Pedersen et al, 2006) to explain the greater displacement of aggression towards triggering out-group members relative to triggering ingroup members. To develop methods of reducing such out-group-directed aggression, we made the following assumption: processes that reduce intergroup bias should also reduce the aggression that is often a consequence of bias.…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations